(untitled) (The Research of Medical Science Review, 2025)
Objective: The primary objective of the study was to evaluate effectiveness of Interprofessional education activities on attitudes of Medical and Midwifery students towards IPE at undergraduate level. Study Design: Mixed quantitative and qualitative study Place and Duration of study: This study was designed to enhance interprofessional collaboration between final year MBBS and midwifery students of CMH Lahore Medical college, National University of Medical Sciences NUMS from May to July 2023. Methods: Three activities were done based on emergency maternity scenarios. Pre and Post sessions attitudes were assessed by Likert scale with five items towards simulation, interprofessional learning, communication, roles and responsibilities and situation awareness. Qualitative survey was done by reflection and feedback of students and colleagues. Results: A total of 100 students 30 Midwifery and 70 MBBS students participated in three IPE simulation activities. Students disclosed level of apprehension on first day of activity. Following the activities, Students reported 100% positive attitude to interprofessional learning, communication and roles and responsibilities with 88% for simulation and 84% for situation awareness. Qualitative survey, reflection and feedback of students commented their positive experience and recognition of need of teamwork, and interprofessional communication in managing these emergency conditions can improve care of women and babies Conclusion: These IPE activities at undergraduate level has protentional to improve their attitudes and experience towards need. of Interprofessional collaboration during emergency situations in workplace so can improve care of woman and babies.